High performance screen printable lithium-ion battery cathode ink based on C-LiFePO4. (1st April 2016) - Sousa, R.E.; Oliveira, J.; Gören, A.; Miranda, D.; Silva, M.M.; Hilliou, Loic; Costa, C.M.; Lanceros-Mendez, S.
Highlights: C-LiFePO4 paste was been prepared for screen-printing technique. The inks produced have a Newtonian viscosity of 3 Pa.s for this printing technique. C-LiFePO4 inks present a 48.2 mAh.g −1 after 50 cycles at 5C. This ink is suitable in the development of printed lithium ion batteries. Abstract: Lithium-ion battery cathodes have been fabricated by screen-printing through the development of C-LiFePO4 inks. It is shown that shear thinning polymer solutions in N-methyl-2-pyrrolidone (NMP) with Newtonian viscosity above 0.4 Pa s are the best binders for formulating a cathode paste with satisfactory film forming properties. The paste shows an elasticity of the order of 500 Pa and, after shear yielding, shows an apparent viscosity of the order of 3 Pa s for shear rates corresponding to those used during screen-printing. The screen-printed cathode produced with a thickness of 26 μm shows a homogeneous distribution of the active material, conductive additive and polymer binder. The total resistance and diffusion coefficient of the cathode are ∼ 450 Ω and 2.5 × 10 −16 cm 2 s −1, respectively. The developed cathodes show an initial discharge capacity of 48.2 mAh g −1 at 5C and a discharge value of 39.8 mAh g −1 after 50 cycles. The capacity retention of 83% represents 23% of the theoretical value (charge and/or discharge process in twenty minutes), demonstrating the good performance of the battery. Thus, the developed C-LiFePO4 based inks allow to fabricate screen-printed cathodes suitable for printed lithium-ion batteries.